2008
DOI: 10.1016/j.bmc.2008.08.072
|View full text |Cite
|
Sign up to set email alerts
|

A study of the structure–activity relationship of GABAA–benzodiazepine receptor bivalent ligands by conformational analysis with low temperature NMR and X-ray analysis

Abstract: The stable conformations of GABAA-benzodiazepine receptor bivalent ligands were determined by low temperature NMR spectroscopy and confirmed by single crystal X-ray analysis. The stable conformations in solution correlated well with those in the solid state. The linear conformation was important for these dimers to access the binding site and exhibit potent in vitro affinity and was illustrated for α5 subtype selective ligands. Bivalent ligands with an oxygen-containing linker folded back upon themselves both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Bivalent ligands have a preferred linker of 3–5 methylene units, between the two pharmacophores (see XLi-093). This was established by NMR experiments run at low temperatures, X-ray crystallography, and molecular modeling of the ligands in question and will be discussed [ 14 , 17 , 18 ].…”
Section: Subtype Selective Ligands For α 5 mentioning
confidence: 99%
See 2 more Smart Citations
“…Bivalent ligands have a preferred linker of 3–5 methylene units, between the two pharmacophores (see XLi-093). This was established by NMR experiments run at low temperatures, X-ray crystallography, and molecular modeling of the ligands in question and will be discussed [ 14 , 17 , 18 ].…”
Section: Subtype Selective Ligands For α 5 mentioning
confidence: 99%
“…Möhler has proposed that α 5 selective inverse agonists or α 5 selective agonists might enhance cognition [ 5 , 13 , 16 – 18 , 86 ]. This is because of the extrasynaptic pyramidal nature of α 5 β 3 γ 2 subtypes, located almost exclusively in the hippocampus.…”
Section: Subtype Selective Agonists For α 5mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note the use of polybutylene glycol spacer groups,73 which have been designed to counter the natural coil‐like conformation obtained when using PEG spacers,7476 whilst retaining an element of hydrophilicity and flexibility. On the other hand, multiple oligoproline residues ( 24 ) have been used to form well‐defined helical structures77 for the synthesis of specifically oriented bivalent ligands with a coiled spacer 69.…”
Section: General Features Of Bivalent Ligandsmentioning
confidence: 99%
“…Among the drugs/compounds used in this patent were the a-5 inverse agonists PWZ029 [65] and XLi356 ( Figure 2) [66]. From a full panel of receptor binding was observed that XLi356 does not bind to other types of receptors and, with PWZ029, were found to reverse scopolamine-induced memory deficit (1 mg/kg) in mice at the dose of 10 mg/kg.…”
Section: Known Compoundsmentioning
confidence: 99%